Preparation method of porous ceramic loaded sulfur-based composite filler and application of porous ceramic loaded sulfur-based composite filler in nitrogen and phosphorus removal of sewage

By layering active components on porous ceramics, the pH contradiction between sulfur autotrophic denitrification and chemical phosphorus removal is resolved, achieving efficient and stable wastewater denitrification and phosphorus removal, extending the filler life and reducing sulfate accumulation.

CN120698601AActive Publication Date: 2025-09-26JIANGSU KUNYI ENVIRONMENTAL ENG CO LTD

Patent Information

Application Number
CN202510747456.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-05
Publication Date
2025-09-26
Estimated Expiration
2045-06-05

AI Technical Summary

Technical Problem

In the existing wastewater denitrification and phosphorus removal technologies, there is a pH contradiction between sulfur autotrophic denitrification and chemical phosphorus removal, the process stability is poor, the sulfur source utilization rate is low, sulfur oxidation inhibits microbial activity, the filler is easily worn, and it is difficult to achieve long-term stable operation.

Method used

Porous ceramics are used as carriers, and active components are loaded in layers through a gradient filling process. The inner layer of siderite composite gel and calcite complex neutralizes H+, the middle layer of pyrite composite gel improves compressive strength, and the outer layer of sulfur-biochar forms nanosulfur crystals to construct a π-π conjugated electron pathway, realizing efficient electron transfer and phosphate precipitation.

Benefits of technology

Without the addition of external carbon sources and pH regulators, it can achieve efficient nitrogen and phosphorus removal, reduce sulfate accumulation, extend the life of the filler, increase the nitrate removal rate and phosphate removal rate, and improve the stability of the filler structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120698601A_ABST
    Figure CN120698601A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sewage treatment, and discloses a preparation method of a porous ceramic loaded sulfur-based composite filler and application of the porous ceramic loaded sulfur-based composite filler in nitrogen and phosphorus removal of sewage. Porous ceramic is taken as a carrier, active components are loaded in a layered manner by adopting a gradient filling process, an inner-layer siderite composite gel and calcite complex dynamically neutralizes H < + > generated by sulfur autotrophy, and pH buffering is realized through sulfo group reversible proton exchange; the compressive strength of the middle-layer pyrite composite gel is improved through C-O-Fe bonding, a Pi-Pi conjugate electron pathway is constructed by polypyrrole-coated hybrid gel, electron transfer is accelerated, and Fe < 2 + > is released to precipitate phosphate; sulfur-charcoal on the outer layer forms nano sulfur crystals, and denitrification is quickly started by utilizing a high specific surface area. Sulfur consumption and sulfate accumulation are reduced through sulfur-iron oxidation-reduction circulation. The filler realizes high-efficiency nitrogen and phosphorus removal of sewage under the condition that a carbon source and a pH regulator are not required to be additionally added.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sewage treatment, and in particular to a method for preparing a porous ceramic-loaded sulfur-based composite filler and its application in sewage denitrification and phosphorus removal. Background Art

[0002] In the field of sewage treatment technology, nitrogen and phosphorus removal are core tasks to ensure the ecological safety of water bodies. Traditional biological denitrification relies on heterotrophic denitrification, which requires additional carbon sources (such as methanol and sodium acetate), which not only increases operating costs but also easily causes secondary pollution; chemical phosphorus removal forms phosphate precipitation by adding iron or aluminum salts, but the agent consumption is large, the sludge output is high, and the residual metal ions may have a negative impact on subsequent processes. The synergistic application of sulfur autotrophic denitrification and chemical precipitation phosphorus removal is a current research hotspot. Sulfur autotrophic denitrification uses sulfur as an electron donor to reduce nitrate, and chemical phosphorus removal relies on iron or aluminum salts to form phosphate precipitates. However, existing technologies face two core challenges: First, the acidic environment (pH < 5.5) generated during sulfur autotrophic denitrification is in conflict with the neutral to weakly alkaline conditions required for chemical phosphorus removal, resulting in poor process stability, frequent pH adjustment, and increased operational complexity; Second, traditional sulfur-iron composite fillers have a single structure, low specific surface area, and sulfur particles that are easily compacted, resulting in low sulfur source utilization. When the sulfate concentration generated by sulfur oxidation exceeds 300 mg / L, it will inhibit microbial activity and further weaken the denitrification efficiency. In addition, the filler is prone to wear (annual wear rate > 5%) and the structure is prone to disintegration, making it difficult to achieve long-term stable operation, which seriously restricts the efficiency and sustainable development of wastewater denitrification and phosphorus removal processes. Summary of the Invention

[0003] In view of the shortcomings of the existing technology, the present application provides a method for preparing a porous ceramic-loaded sulfur-based composite filler and its application in wastewater denitrification and phosphorus removal. The porous ceramic is used as a carrier, and a gradient filling process is adopted to load the active components in layers. The inner layer of siderite composite gel and calcite composite dynamically neutralizes the H generated by sulfur autotrophic + The pH buffer is achieved through reversible proton exchange of sulfonic acid groups; the middle pyrite composite gel improves the compressive strength through CO-Fe bonding, and the polypyrrole-coated hybrid gel constructs a π-π conjugated electron pathway to accelerate electron transfer and release Fe 2+ Phosphate precipitation; the outer sulfur-biochar layer forms nano-sulfur crystals, leveraging its high surface area to rapidly initiate denitrification. The sulfur-iron redox cycle reduces sulfur consumption and sulfate accumulation. This filler achieves efficient nitrogen and phosphorus removal from wastewater without the need for an external carbon source or pH regulator.

[0004] To achieve the above objectives, this application adopts the following technical solutions:

[0005] In a first aspect, the present application provides a method for preparing a porous ceramic-loaded sulfur-based composite filler, comprising the following steps:

[0006] The sulfur is melted and mixed with rice husk biochar, and then vacuum impregnated and solidified to obtain a composite sulfur-carbon material;

[0007] A lignin sulfonic acid gel is prepared using a lignin sulfonic acid gel precursor solution containing iron ions, and a polypyrrole layer is coated on the surface of the lignin sulfonic acid gel to obtain a hybrid gel;

[0008] Ultrasonic compounding of pyrite powder and the hybrid gel to obtain pyrite composite gel; ball milling compounding of siderite powder and the hybrid gel to obtain siderite composite gel;

[0009] The mixed powder obtained by mixing the siderite composite gel and calcite powder is covered on the surface of the porous ceramic substrate, and the inner layer filled porous ceramic is obtained by cold isostatic pressing; the pyrite composite gel is filled into the inner layer filled porous ceramic by vibration filling to obtain a middle layer filled porous ceramic;

[0010] Mixing the middle layer filled porous ceramic, the composite sulfur-carbon material and the lignin sulfonic acid gel precursor to obtain an outer layer filled porous ceramic;

[0011] The porous ceramic filled with the outer layer is subjected to gradient heat treatment and acid washing treatment to obtain the porous ceramic loaded sulfur-based composite filler.

[0012] In a second aspect, the present application provides a method for preparing a porous ceramic-loaded sulfur-based composite filler and the application of the prepared porous ceramic-loaded sulfur-based composite filler in wastewater denitrification and phosphorus removal.

[0013] Beneficial technical effects:

[0014] In this scheme, a porous ceramic matrix is ​​first prepared with clay, sawdust and sodium silicate, and then the active components are loaded layer by layer using a gradient filling process. The inner layer of siderite composite gel and calcite composite continuously releases Fe 2+ and buffer the pH; the middle layer of pyrite composite gel constructs a high-speed electron transfer pathway; the outer layer of sulfur-biochar material quickly releases electrons through nano-sulfur crystals to initiate denitrification. By introducing sodium lignin sulfonate gel with a network structure, a uniform loading base is provided for polypyrrole, and the resulting hybrid gel can have a uniformly distributed π-π conjugated electron pathway. At the same time, the pH of the system can be adjusted by the sulfonic acid group itself, avoiding the influence of the additional introduction of pH regulators on the conjugated electron pathway, thereby extending the working life of the uniformly distributed conjugated electron pathway. This scheme uses a porous ceramic-loaded sulfur-based composite filler constructed by gradient loading to achieve efficient nitrogen and phosphorus removal, low sulfate accumulation, and a long service life in sewage treatment without the addition of an external carbon source and pH regulator. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a schematic diagram of the preparation method of the porous ceramic-loaded sulfur-based composite filler of the present invention.

[0016] Figure 2 This is a trend chart of sulfate concentration changes in Example 4 of the present invention when the porous ceramic-supported sulfur-based composite filler is continuously operated for 180 days in the wastewater denitrification and phosphorus removal application. DETAILED DESCRIPTION

[0017] In order to make the technical problems, technical solutions, and beneficial effects to be solved by this application more clearly understood, the present application is further described in detail below with reference to the following examples. However, this should not be construed as limiting the scope of this application to the following examples. Without departing from the above-mentioned method concepts of this application, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of this application.

[0018] In this application, the terms used in this application are for the purpose of describing specific embodiments only and are not intended to be limiting of the application.

[0019] As used in this application, the singular forms "for," "or," "an," "any," and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0020] In addition, the terms “first” and “second”, if used, are only used for descriptive purposes and should not be understood as indicating or implying relative importance.

[0021] In a first aspect, the present application provides a method for preparing a porous ceramic-loaded sulfur-based composite filler, comprising the following steps:

[0022] The sulfur is melted and mixed with rice husk biochar, and then vacuum impregnated and solidified to obtain a composite sulfur-carbon material;

[0023] A lignin sulfonic acid gel is prepared using a lignin sulfonic acid gel precursor solution containing iron ions, and a polypyrrole layer is coated on the surface of the lignin sulfonic acid gel to obtain a hybrid gel;

[0024] Ultrasonic compounding of pyrite powder and the hybrid gel to obtain pyrite composite gel; ball milling compounding of siderite powder and the hybrid gel to obtain siderite composite gel;

[0025] The mixed powder obtained by mixing the siderite composite gel and calcite powder is covered on the surface of the porous ceramic substrate, and the inner layer filled porous ceramic is obtained by cold isostatic pressing; the pyrite composite gel is filled into the inner layer filled porous ceramic by vibration filling to obtain a middle layer filled porous ceramic;

[0026] Mixing the middle layer filled porous ceramic, the composite sulfur-carbon material and the lignin sulfonic acid gel precursor to obtain an outer layer filled porous ceramic;

[0027] The porous ceramic filled with the outer layer is subjected to gradient heat treatment and acid washing treatment to obtain the porous ceramic loaded sulfur-based composite filler.

[0028] The high-porosity porous ceramic matrix prepared from clay, sawdust and sodium silicate was used as the carrier, and the active components were loaded layer by layer using a gradient filling process. The inner siderite composite gel was exposed to CO3 dissolved in calcite. 2- Dynamically neutralize H produced by sulfur autotrophy + At the same time, the sulfonic acid group -SO3H in the hybrid gel achieves dynamic pH buffering through reversible proton exchange, stabilizes the pH of the system, avoids the problem of microbial inactivation caused by pH < 5.5 in traditional processes, and extends the life of the filler; the middle layer is a pyrite composite gel, and the hybrid gel and pyrite interface are chemically bonded through CO-Fe to improve the compressive strength and reduce the risk of filler wear; the outer layer of sulfur-biochar composite is quenched by liquid nitrogen to form nanosulfur crystals. The high specific surface area and high reaction activity of nanosulfur enable the denitrification reaction to start quickly, thereby increasing the nitrate NO3 - -N removal rate. In addition, the Fe 2+ / S 0 The redox cycle achieves efficient electron utilization, and the slow release of Fe from siderite 2+ Oxidized to Fe 3+ After that, with S in sulfide 2- Reaction regeneration Fe 2+ And generate elemental sulfur S 0 , forming a closed cycle, which reduces sulfur consumption and reduces sulfate SO4 2- concentration; the synchronously generated Fe(OH)3 colloid and hydroxyapatite Ca5(PO4)3OH enhance phosphorus removal through adsorption-coprecipitation, and the components work together to achieve efficient nitrogen and phosphorus removal effects on wastewater.

[0029] In a feasible implementation scenario, the rice husk biochar is prepared by pyrolyzing rice husk at 500-700° C. for 1.5-3 hours in a nitrogen atmosphere, and the mass ratio of the rice husk biochar to the sulfur is 1:(2-4); and the vacuum impregnation time is 1-2 hours.

[0030] In a feasible implementation scenario, the preparation method of the hybrid gel includes: preparing a 4-6wt% sodium lignin sulfonate solution, adding a 0.15-0.20mol / L ferric chloride solution to a pH of 2.8-3.2 to obtain the sodium lignin sulfonate gel precursor solution, and letting it stand for 10-12 hours to obtain the lignin sulfonic acid gel; mixing ethanol and water in a volume ratio of 1:1 to obtain a mixed solvent, and using the mixed solvent to prepare a 0.55-0.65mol / L pyrrole solution; immersing the lignin sulfonic acid gel in the pyrrole solution, introducing chlorine gas at a flow rate of 0.4-0.6L / min, reacting at room temperature for 4-6 hours, and then freeze-drying at -50°C for 4-6 hours.

[0031] Sodium lignin sulfonate gel 3+ A cross-linked network is formed, and the surface-coated polypyrrole layer constructs a π-π conjugated electron pathway, achieving the effect of inorganic sulfur supplying electrons and organic hybrid gel transferring electrons, thereby increasing the electron migration rate and releasing Fe 2+ It reacts with phosphate to form Fe3(PO4)2 precipitate, thus improving the total phosphorus TP removal rate.

[0032] In a feasible implementation scenario, the preparation method of the pyrite composite gel includes: adding 0.1wt%-0.12wt% of polyethylene glycol PEG-4000 to a mixed system in which pyrite powder and the hybrid gel are mixed in a mass ratio of (4-6):1, ultrasonicating for 20-30 minutes, and vacuum drying at 60-80°C for 12-24 hours to obtain the pyrite composite gel; the preparation process of the siderite composite gel includes: mixing the siderite powder and the hybrid gel in a mass ratio of (1.5-2.5):1, ball milling for 1-2 hours, and heating at 100-120°C for 30-60 minutes to obtain the siderite composite gel.

[0033] In a feasible implementation scenario, the preparation method of the inner layer filled porous ceramic includes: mixing siderite composite gel and calcite powder in a mass ratio of (1.8-3):1 to obtain a mixed powder, spreading the porous ceramic matrix in a mold, evenly spreading the mixed powder, the mass ratio of the porous ceramic matrix to the mixed powder is 1:(0.6-0.8), cold isostatic pressing at a pressure of 8-10MPa for 10-15min, and gently sweeping the surface with a soft brush to remove unbound loose particles to obtain the inner layer filled porous ceramic.

[0034] In a feasible implementation scenario, the preparation method of the middle-layer filled porous ceramic includes: loading the pyrite composite gel and the inner-layer filled porous ceramic into the hopper of a vibrating filling machine in a mass ratio of 1:(4-5), setting the amplitude to 25-30Hz and the vibration time to 20-30min to obtain the middle-layer filled porous ceramic.

[0035] In a feasible implementation scenario, the preparation method of the outer layer filled porous ceramic includes: placing the middle layer filled porous ceramic into a fluidized bed, introducing nitrogen, then placing the composite sulfur-carbon material preheated to 60°C into the fluidized bed, atomizing the sodium lignin sulfonate gel precursor through a two-fluid nozzle, and uniformly spraying at a rate of 0.2-0.4 mL / min; immediately turning on the liquid nitrogen cooling system after the spraying is completed to obtain the outer layer filled porous ceramic; the mass ratio of the middle layer filled porous ceramic, the composite sulfur-carbon material and the sodium lignin sulfonate gel precursor is 8:(1-1.2):(0.2-0.4).

[0036] In a feasible implementation scenario, the gradient heat treatment includes: placing the outer layer filled porous ceramic into a programmable temperature furnace, heating the temperature to 100-120°C at 5-8°C / min under a nitrogen atmosphere and keeping it warm for 30-40 minutes, continuing to heat the temperature to 140-160°C and keeping it warm for 20-30 minutes, then heating the temperature to 200-220°C at 10°C / min and keeping it warm for 10-15 minutes, and cooling to room temperature.

[0037] In a feasible implementation scenario, the pickling treatment includes: placing the outer filling porous ceramic that has undergone the gradient heat treatment into a drum-type reactor, spraying 5-8wt% citric acid solution while rolling, and the mass ratio of citric acid solution to the outer layer filling porous ceramic is (0.5-2):1, and obtaining the porous ceramic-loaded sulfur-based composite filler after drying.

[0038] In a second aspect, the present application provides a method for preparing a porous ceramic-loaded sulfur-based composite filler and the application of the prepared porous ceramic-loaded sulfur-based composite filler in wastewater denitrification and phosphorus removal.

[0039] The following will describe in detail a method for preparing a porous ceramic-loaded sulfur-based composite filler provided by the present application and its application in wastewater denitrification and phosphorus removal in combination with different embodiments.

[0040] Embodiment 1:

[0041] like Figure 1 As shown, a method for preparing a porous ceramic-loaded sulfur-based composite filler comprises the following steps:

[0042] 1. Mix 200-mesh clay, sawdust (≤1 mm in size), and sodium silicate in a mass ratio of 6:3:1. Use a screw extruder to form pellets with a diameter of 3 mm. Heat the mixture to 1100°C at a rate of 10°C / min and hold for 2 hours to obtain a porous ceramic matrix.

[0043] 2. After cleaning the rice husk, pyrolyze it at 500°C under a nitrogen atmosphere for 3 hours, pass it through a 200-mesh sieve to obtain rice husk biochar, melt sulfur at 140°C and mix it with the rice husk biochar in a mass ratio of 2:1, vacuum impregnate it for 1 hour, and cool it with liquid nitrogen to solidify it to obtain a composite sulfur-carbon material;

[0044] 3. Prepare a 4 wt% sodium lignin sulfonate solution, add 0.15 mol / L ferric chloride solution to a pH of 2.8 to obtain a sodium lignin sulfonate gel precursor solution, and let it stand for 10 hours to obtain a lignin sulfonate gel; mix ethanol and water in a volume ratio of 1:1 to obtain a mixed solvent, and use the mixed solvent to prepare a 0.55 mol / L pyrrole solution; immerse the lignin sulfonate gel in the pyrrole solution, introduce chlorine gas at a flow rate of 0.4 L / min, react at room temperature for 4 hours, wash with deionized water until neutral, and freeze-dry at -50°C for 4 hours to obtain a hybrid gel;

[0045] 4. To a mixture of 200-mesh pyrite powder and the hybrid gel at a mass ratio of 4:1, 0.1 wt% polyethylene glycol PEG-4000 was added, the mixture was ultrasonicated at 40 kHz for 20 min, and vacuum dried at 60°C for 24 h to obtain a pyrite composite gel; 100-mesh siderite powder and the hybrid gel were mixed at a mass ratio of 1.5:1, ball milled at 300 rpm for 1 h, and heated at 120°C for 30 min to obtain a siderite composite gel;

[0046] 5. The siderite composite gel and 200-mesh calcite powder were mixed at a mass ratio of 1.8:1 to obtain a mixed powder. The porous ceramic matrix was spread flat in the mold and the mixed powder was evenly sprinkled. The mass ratio of the porous ceramic matrix to the mixed powder was 1:0.6. The mold was cold isostatically pressed at a pressure of 8 MPa for 10 minutes. The surface was gently brushed with a soft brush to remove unbound loose particles to obtain an inner layer filled with porous ceramic.

[0047] 6. The pyrite composite gel and the inner layer porous ceramic filling were loaded into the vibrating filling machine hopper at a mass ratio of 1:4, and the amplitude was set to 25 Hz and the vibration time was set to 30 min to obtain the middle layer porous ceramic filling;

[0048] 7. The porous ceramic filled in the middle layer is put into the fluidized bed, and nitrogen with a flow rate of 0.8m / s is introduced. Then the composite sulfur-carbon material preheated to 60°C is put into the fluidized bed, and the sodium lignin sulfonate gel precursor is atomized into 50μm droplets through a two-fluid nozzle.

[0049] mL / min rate of uniform spraying, the middle layer is filled with porous ceramics, composite sulfur-carbon materials and sodium lignin sulfonate gel in a mass ratio of 8:1:0.2, and the liquid nitrogen cooling system is immediately turned on after the spraying is completed to obtain the outer layer filled with porous ceramics;

[0050] 8. The outer layer filled porous ceramic is placed in a programmable temperature-controlled furnace, heated to 100°C at 5°C / min under a nitrogen atmosphere, kept warm for 30 minutes, continued to heat to 140°C and kept warm for 20 minutes, heated to 200°C at 10°C / min and kept warm for 10 minutes, and then cooled to room temperature and placed in a drum reactor. It is rolled at a linear speed of 0.5 m / s and sprayed with 5 wt% citric acid solution at the same time. The mass ratio of citric acid solution to the outer layer filled porous ceramic is 0.5:1. After 2 hours, it is washed with deionized water until neutral and dried to obtain the porous ceramic-loaded sulfur-based composite filler.

[0051] Example 2

[0052] like Figure 1 As shown, a method for preparing a porous ceramic-loaded sulfur-based composite filler comprises the following steps:

[0053] 1. Mix 200-mesh clay, sawdust (≤1 mm in size), and sodium silicate in a mass ratio of 6:3:1. Use a screw extruder to form pellets with a diameter of 3 mm. Heat the mixture to 1100°C at a rate of 10°C / min and hold for 2 hours to obtain a porous ceramic matrix.

[0054] 2. After cleaning the rice husk, pyrolyze it at 600°C for 2 hours under a nitrogen atmosphere and pass it through a 200-mesh sieve to obtain rice husk biochar. Then, melt sulfur at 140°C and mix it with the rice husk biochar in a mass ratio of 3:1. The mixture is vacuum impregnated for 1.5 hours and solidified by cooling with liquid nitrogen to obtain a composite sulfur-carbon material.

[0055] 3. Prepare a 5 wt% sodium lignin sulfonate solution, add 0.18 mol / L ferric chloride solution to a pH of 3.0 to obtain a sodium lignin sulfonate gel precursor solution, and let it stand for 11 hours to obtain a lignin sulfonate gel; mix ethanol and water in a volume ratio of 1:1 to obtain a mixed solvent, and use the mixed solvent to prepare a 0.6 mol / L pyrrole solution; immerse the lignin sulfonate gel in the pyrrole solution, introduce chlorine gas at a flow rate of 0.5 L / min, react at room temperature for 5 hours, wash with deionized water until neutral, and freeze-dry at -50°C for 5 hours to obtain a hybrid gel;

[0056] 4. 200-mesh pyrite powder was mixed with the hybrid gel at a mass ratio of 5:1, 0.11 wt% polyethylene glycol PEG-4000 was added, 40 kHz ultrasound was applied for 25 min, and vacuum dried at 70°C for 18 h to obtain a pyrite composite gel; 100-mesh siderite powder was mixed with the hybrid gel at a mass ratio of 2:1, ball milled at 300 rpm for 1.5 h, and heated at 110°C for 45 min to obtain a siderite composite gel;

[0057] 5. The siderite composite gel and 200-mesh calcite powder were mixed at a ratio of 2.4:1 to obtain a mixed powder. The porous ceramic matrix was spread flat in the mold and the mixed powder was evenly sprinkled. The mass ratio of the porous ceramic matrix to the mixed powder was 1:0.7. The mold was cold isostatically pressed at a pressure of 9 MPa for 12 minutes. The surface was gently brushed with a soft brush to remove unbound loose particles to obtain an inner layer filled with porous ceramic.

[0058] 6. The pyrite composite gel and the inner layer porous ceramic filling were loaded into the vibrating filling machine hopper at a mass ratio of 1:4.5, and the amplitude was set to 30 Hz and the vibration time was set to 25 min to obtain the middle layer porous ceramic filling;

[0059] 7. The middle layer of porous ceramic filling was placed in a fluidized bed, nitrogen was introduced at a flow rate of 0.8 m / s, and then the composite sulfur-carbon material preheated to 60° C. was placed in the fluidized bed. The sodium lignin sulfonate gel precursor was atomized into 50 μm droplets through a two-fluid nozzle and sprayed evenly at a rate of 0.3 mL / min. The mass ratio of the middle layer of porous ceramic filling, the composite sulfur-carbon material, and the sodium lignin sulfonate gel was 8:1.1:0.3. After the spraying was completed, the liquid nitrogen cooling system was immediately turned on to obtain the outer layer of porous ceramic filling;

[0060] 8. The outer layer of porous ceramic filling was placed in a programmable temperature-controlled furnace, heated to 110°C at 6°C / min under a nitrogen atmosphere, kept warm for 35 minutes, continued to heat to 150°C and kept warm for 25 minutes, and then heated to 210°C at 10°C / min and kept warm for 15 minutes. After cooling to room temperature, it was placed in a drum reactor and rolled at a linear speed of 0.5 m / s. At the same time, 6 wt% citric acid solution was sprayed. The mass ratio of citric acid solution to the outer layer of porous ceramic filling was 1:1. After 2 hours, it was washed with deionized water until neutral and dried to obtain the porous ceramic-loaded sulfur-based composite filler.

[0061] Example 3

[0062] like Figure 1 As shown, a method for preparing a porous ceramic-loaded sulfur-based composite filler comprises the following steps:

[0063] 1. Mix 200-mesh clay, sawdust with a particle size of ≤1 mm, and sodium silicate in a mass ratio of 6:3:1. Use a screw extruder to form particles with a diameter of 3 mm. Heat the mixture to 1100°C at a rate of 10°C / min and hold for 2 hours to obtain a porous ceramic matrix.

[0064] 2. After cleaning the rice husk, pyrolyze it at 700°C under a nitrogen atmosphere for 1.5 hours, pass it through a 200-mesh sieve, and obtain rice husk biochar. Then, melt sulfur at 140°C and mix it with the rice husk biochar in a mass ratio of 4:1. The mixture is vacuum impregnated for 2 hours and solidified by cooling with liquid nitrogen to obtain a composite sulfur-carbon material.

[0065] 3. A 6 wt% sodium lignin sulfonate solution was prepared, and a 0.20 mol / L ferric chloride solution was added to a pH of 3.2 to obtain a sodium lignin sulfonate gel precursor solution, which was allowed to stand for 12 hours to obtain a lignin sulfonate gel. A mixed solvent was prepared by mixing ethanol and water in a volume ratio of 1:1, and a 0.65 mol / L pyrrole solution was prepared with the mixed solvent. The lignin sulfonate gel was immersed in the pyrrole solution, and chlorine gas was introduced at a flow rate of 0.6 L / min. The reaction was carried out at room temperature for 6 hours, and the mixture was washed with deionized water until neutral. The mixture was freeze-dried at -50°C for 6 hours to obtain a hybrid gel.

[0066] 4. 200-mesh pyrite powder was mixed with the hybrid gel at a mass ratio of 6:1, 0.12 wt% polyethylene glycol PEG-4000 was added, 40 kHz ultrasound was applied for 30 min, and vacuum drying was performed at 80°C for 12 h to obtain a pyrite composite gel; 100-mesh siderite powder was mixed with the hybrid gel at a mass ratio of 2.5:1, ball milled at 300 rpm for 2 h, and de-heated at 100°C for 60 min to obtain a siderite composite gel;

[0067] 5. The siderite composite gel and 200-mesh calcite powder were mixed in a ratio of 3:1 to obtain a mixed powder. The porous ceramic matrix was spread flat in the mold and the mixed powder was evenly spread. The mass ratio of the porous ceramic matrix to the mixed powder was 1:0.8. The mold was cold isostatically pressed at a pressure of 10 MPa for 15 minutes. The surface was gently brushed with a soft brush to remove unbound loose particles to obtain an inner layer filled with porous ceramic.

[0068] 6. The pyrite composite gel and the inner layer porous ceramic filling were loaded into the vibrating filling machine hopper at a mass ratio of 1:5, and the amplitude was set to 30 Hz and the vibration time was set to 20 min to obtain the middle layer porous ceramic filling;

[0069] 7. The middle layer of porous ceramic filling was placed in a fluidized bed, nitrogen was introduced at a flow rate of 0.8 m / s, and then the composite sulfur-carbon material preheated to 60° C. was placed in the fluidized bed. The sodium lignin sulfonate gel precursor was atomized into 50 μm droplets through a two-fluid nozzle and sprayed evenly at a rate of 0.4 mL / min. The mass ratio of the middle layer of porous ceramic filling, the composite sulfur-carbon material, and the sodium lignin sulfonate gel was 8:1.2:0.4. After the spraying was completed, the liquid nitrogen cooling system was immediately turned on to obtain the outer layer of porous ceramic filling;

[0070] 8. The outer layer filled porous ceramic is placed in a programmable temperature-controlled furnace, heated to 120°C at 8°C / min under a nitrogen atmosphere, kept warm for 40 minutes, continued to heat to 160°C and kept warm for 30 minutes, heated to 220°C at 10°C / min and kept warm for 15 minutes, and then placed in a drum-type reactor after cooling to room temperature. It is rolled at a linear speed of 0.5 m / s and sprayed with 8wt% citric acid solution at the same time. The mass ratio of citric acid solution to the outer layer filled porous ceramic is 2:1. After 2 hours, it is washed with deionized water until neutral and dried to obtain the porous ceramic-loaded sulfur-based composite filler.

[0071] Example 4

[0072] Application of a porous ceramic-loaded sulfur-based composite filler in wastewater denitrification and phosphorus removal.

[0073] The porous ceramic-supported sulfur-based composite filler prepared in Example 1 was loaded into an upflow fixed bed with a filling rate of 60%. The influent water quality was: nitrate NO3 - -N=25mg / L, total phosphorus TP=3mg / L, pH=6.8, operating parameters: HRT=2h, backwash cycle 30 days; record the effluent indicators and calculate the removal rate, record the filler life, and the results are shown in Table 1.

[0074] Example 5

[0075] Application of a porous ceramic-loaded sulfur-based composite filler in wastewater denitrification and phosphorus removal.

[0076] The implementation parameters and steps are the same as those of Example 4. The difference from Example 4 is that the porous ceramic-loaded sulfur-based composite filler of Example 1 is replaced by the porous ceramic-loaded sulfur-based composite filler of Example 2.

[0077] Example 6

[0078] Application of a porous ceramic-loaded sulfur-based composite filler in wastewater denitrification and phosphorus removal.

[0079] The implementation parameters and steps are the same as those of Example 4. The difference from Example 4 is that the porous ceramic-loaded sulfur-based composite filler of Example 1 is replaced by the porous ceramic-loaded sulfur-based composite filler of Example 3.

[0080] Comparative Example 1

[0081] A method for preparing a porous ceramic-loaded sulfur-based composite filler, wherein the implementation parameters and steps are the same as those of Example 1, except that no hybrid gel is added.

[0082] Comparative Example 2:

[0083] A method for preparing a porous ceramic-loaded sulfur-based composite filler, wherein the implementation parameters and steps are the same as those of Example 1, except that layered filling is not performed.

[0084] Comparative Example 3

[0085] A method for preparing a porous ceramic-loaded sulfur-based composite filler, wherein the implementation parameters and steps are the same as those of Example 1, except that siderite and pyrite are not added.

[0086] Comparative Example 4

[0087] A method for preparing a porous ceramic-loaded sulfur-based composite filler, wherein the implementation parameters and steps are the same as those of Example 1, except that no polypyrrole layer coating is performed.

[0088] Comparative Example 5

[0089] Application of a porous ceramic-loaded sulfur-based composite filler in wastewater denitrification and phosphorus removal.

[0090] The implementation parameters and steps are the same as those of Example 4. The difference from Example 4 is that the porous ceramic-loaded sulfur-based composite filler of Example 1 is replaced by the porous ceramic-loaded sulfur-based composite filler of Comparative Example 1. The results are shown in Table 1.

[0091] Comparative Example 6

[0092] Application of a porous ceramic-loaded sulfur-based composite filler in wastewater denitrification and phosphorus removal.

[0093] The implementation parameters and steps are the same as those of Example 4. The difference from Example 4 is that the porous ceramic-loaded sulfur-based composite filler of Example 1 is replaced by the porous ceramic-loaded sulfur-based composite filler of Comparative Example 2. The results are shown in Table 1.

[0094] Comparative Example 7

[0095] Application of a porous ceramic-loaded sulfur-based composite filler in wastewater denitrification and phosphorus removal.

[0096] The implementation parameters and steps are the same as those of Example 4. The difference from Example 4 is that the porous ceramic-loaded sulfur-based composite filler of Example 1 is replaced by the porous ceramic-loaded sulfur-based composite filler of Comparative Example 3. The results are shown in Table 1.

[0097] Comparative Example 8

[0098] Application of a porous ceramic-loaded sulfur-based composite filler in wastewater denitrification and phosphorus removal.

[0099] The implementation parameters and steps are the same as those of Example 4. The difference from Example 4 is that the porous ceramic-loaded sulfur-based composite filler of Example 1 is replaced with the porous ceramic-loaded sulfur-based composite filler of Comparative Example 4. The results are shown in Table 1.

[0100] Table 1 Denitrification and phosphorus removal test results

[0101]

[0102]

[0103] As shown in Table 1, the porous ceramic-supported sulfur-based composite fillers of Examples 4 to 6 have a significant effect on the removal of NO3 in the wastewater nitrogen and phosphorus removal test. - -N removal rate ≥92.8%, TP removal rate ≥90.3%, SO4 2- Accumulation ≤ 137mg / L, the packing life is 5 years. Comparative Examples 5-8 have significantly reduced denitrification and phosphorus removal efficiency, NO3 - -N removal rate <80.0%, TP removal rate <72.3%, SO4 2- The accumulation was ≥205 mg / L, and the filler life was significantly shortened compared with the example.

[0104] Performance testing:

[0105] The specific surface areas of the porous ceramic-supported sulfur-based composite fillers prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested by BET according to ASTM D3663. The results are shown in Table 2.

[0106] The sulfur loading rates of the porous ceramic-supported sulfur-based composite fillers prepared by Examples 1 to 3 and Comparative Examples 1 to 4 were tested according to ASTM E1019. The results are shown in Table 2.

[0107] The compressive strength of the porous ceramic-supported sulfur-based composite fillers prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was tested according to ISO 18591. The results are shown in Table 2.

[0108] The Fe content of the porous ceramic-supported sulfur-based composite fillers prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was measured by atomic absorption spectroscopy according to EPA6010. 2+ The results of sustained release rate are shown in Table 2.

[0109] Table 2 Performance test results

[0110]

[0111]

[0112] As shown in Table 2, the specific surface areas of the porous ceramic-supported sulfur-based composite fillers prepared in Examples 1 to 3 are 782-854 m 2 / g, sulfur loading rate 34% to 38%, compressive strength 9.94-12.71MPa, Fe 2+ The sustained release rate is 0.12-0.17 mg / (g·d). The specific surface area of ​​the porous ceramic-loaded sulfur-based composite fillers prepared in Comparative Examples 1 to 4 is 553-662 m 2 / g, sulfur loading rate 20% to 29%, compressive strength 5.33-8.46MPa, Fe 2+ The sustained-release rate is 0.03-0.58 mg / (g·d).

[0113] The porous ceramic-supported sulfur-based composite fillers in Comparative Examples 1 and 5 were not introduced with hybrid gel. As shown in Tables 1 and 2, the denitrification and phosphorus removal efficiency decreased significantly. - The -N removal rate was 66.0%, the TP removal rate was 60.0%, and the packing life was shortened to 2 years. The hybrid gel made from lignin sulfonic acid gel combined with polypyrrole is a key medium for electron transfer. Without it, the conductive network is lost, electron migration rate is reduced, and sulfur autotrophic denitrification is hindered. Furthermore, the sulfonic acid groups in the gel lose their ability to dynamically regulate pH, leading to acidification of the system and accelerated packing corrosion, shortening its life.

[0114] In Comparative Examples 2 and 6, the porous ceramic-supported sulfur-based composite filler was not filled in layers, and NO3 - -N removal rate was 80.0%, and sulfate accumulation was high at 205 mg / L. The layered filling design of the outer sulfur-carbon material, the middle pyrite composite gel, and the inner calcite composite achieved synergistic effects through gradient electron release and buffering pH. When not layered, the mixing of the components led to excessive sulfur oxidation, SO4 2- The accumulation amount increases, and the pH adjustment capacity is insufficient, resulting in an imbalance between denitrification and phosphorus removal efficiency.

[0115] In comparative examples 3 and 7, the porous ceramic-supported sulfur-based composite fillers were not added with siderite and pyrite, and the TP removal rate dropped significantly to 47.3%. 2+ The sustained release rate is extremely low, only 0.03 mg / (g·d). Siderite and pyrite are Fe 2+ The main source of Fe 2+ By chemically precipitating FePO4 and catalyzing sulfur oxidation, electron transfer is promoted to achieve dual-action phosphorus removal; when it is missing, the phosphorus precipitation efficiency is reduced, and the sulfur autotrophic denitrification lacks a catalyst, and the simultaneous denitrification is limited.

[0116] The porous ceramic-supported sulfur-based composite fillers in Comparative Examples 4 and 8 were not coated with a polypyrrole layer, and the compressive strength decreased to 8.46 MPa, the electron transfer rate decreased, and the Fe 2+ The sustained release rate is 0.37 mg / (g·d). The polypyrrole layer enhances the conductivity of the gel through π-π conjugation. The lack of its coating leads to the obstruction of the electron transfer path, the reduction of the interfacial bonding strength between pyrite and gel, the decrease of compressive strength, and the decrease of Fe 2+ The release rate decreases, affecting the synergistic efficiency of phosphorus precipitation and sulfur oxidation reactions.

[0117] In addition, the loaded upflow fixed bed of Example 4 was used for sewage treatment and operated continuously for 180 days. The change of sulfate concentration was recorded every 15 days. The results are as follows: Figure 2 As shown, the sulfate concentration of the effluent from the system of the present invention is stable at below 250 mg / L, which meets the requirements of the "Surface Water Environmental Quality Standard".

[0118] The above results show and describe the basic principles and main features of this application as well as the advantages of this application.

[0119] Those skilled in the art should understand that the present application is not limited to the above-described embodiments. The above-described embodiments and descriptions are merely illustrative of the principles of the present application. Various changes and improvements may be made to the present application without departing from the spirit and scope of the present application. Such changes and improvements are intended to fall within the scope of the present application. The scope of protection claimed in the present application is defined by the equivalents of the appended claims.

Claims

1. A method for preparing a porous ceramic-loaded sulfur-based composite filler, characterized in that: The following steps are involved: The sulfur is melted and mixed with rice husk biochar, and then vacuum impregnated and solidified to obtain a composite sulfur-carbon material; A lignin sulfonic acid gel is prepared using a lignin sulfonic acid gel precursor solution containing iron ions, and a polypyrrole layer is coated on the surface of the lignin sulfonic acid gel to obtain a hybrid gel; Ultrasonic compounding of pyrite powder and the hybrid gel to obtain pyrite composite gel; ball milling compounding of siderite powder and the hybrid gel to obtain siderite composite gel; The mixed powder obtained by mixing the siderite composite gel and calcite powder is covered on the surface of the porous ceramic substrate, and the inner layer filled porous ceramic is obtained by cold isostatic pressing; the pyrite composite gel is filled into the inner layer filled porous ceramic by vibration filling to obtain a middle layer filled porous ceramic; Mixing the middle layer filled porous ceramic, the composite sulfur-carbon material and the lignin sulfonic acid gel precursor to obtain an outer layer filled porous ceramic; The porous ceramic filled with the outer layer is subjected to gradient heat treatment and acid washing treatment to obtain the porous ceramic loaded sulfur-based composite filler.

2. The method for preparing a porous ceramic-loaded sulfur-based composite filler according to claim 1, characterized in that: The rice husk biochar is prepared by pyrolyzing rice husk at 500-700° C. for 1.5-3 hours in a nitrogen atmosphere. The mass ratio of the rice husk biochar to the sulfur is 1:(2-4). The vacuum impregnation time is 1-2 hours.

3. The method for preparing a porous ceramic-supported sulfur-based composite filler according to claim 1, characterized in that: The preparation method of the hybrid gel includes: adding 0.15-0.20 mol / L ferric chloride solution to a 4-6 wt% sodium lignin sulfonate solution until the pH is 2.8-3.2 to obtain the sodium lignin sulfonate gel precursor solution, and letting it stand for 10-12 hours to obtain the lignin sulfonic acid gel; mixing ethanol and water in a volume ratio of 1:1 to obtain a mixed solvent, and using the mixed solvent to prepare a 0.55-0.65 mol / L pyrrole solution; immersing the lignin sulfonic acid gel in the pyrrole solution, introducing chlorine gas, reacting at room temperature for 4-6 hours, and then freeze-drying at -50°C for 4-6 hours.

4. The method for preparing a porous ceramic-supported sulfur-based composite filler according to claim 1, characterized in that: The preparation method of the pyrite composite gel comprises: adding 0.1wt%-0.12wt% of polyethylene glycol PEG-4000 to a mixed system of pyrite powder and the hybrid gel in a mass ratio of (4-6):1, ultrasonicating for 20-30 minutes, and vacuum drying at 60-80°C for 12-24 hours to obtain the pyrite composite gel; the preparation process of the siderite composite gel comprises: mixing the siderite powder and the hybrid gel in a mass ratio of (1.5-2.5):1, ball milling for 1-2 hours, and heating at 100-120°C for 30-60 minutes to obtain the siderite composite gel.

5. The method for preparing a porous ceramic-loaded sulfur-based composite filler according to claim 1, characterized in that: The preparation method of the inner layer filled porous ceramic includes: mixing siderite composite gel and calcite powder in a mass ratio of (1.8-3):1 to obtain a mixed powder, spreading a porous ceramic matrix in a mold, evenly spreading the mixed powder, wherein the mass ratio of the porous ceramic matrix to the mixed powder is 1:(0.6-0.8), cold isostatic pressing is performed at a pressure of 8-10 MPa for 10-15 minutes, and lightly sweeping the surface with a soft brush to remove unbound loose particles to obtain the inner layer filled porous ceramic.

6. The method for preparing a porous ceramic-supported sulfur-based composite filler according to claim 1, characterized in that: The preparation method of the middle-layer filled porous ceramic comprises: loading the pyrite composite gel and the inner-layer filled porous ceramic into a vibrating filling machine hopper at a mass ratio of 1:(4-5), setting the amplitude to 25-30 Hz and the vibration time to 20-30 min, to obtain the middle-layer filled porous ceramic.

7. The method for preparing a porous ceramic-loaded sulfur-based composite filler according to claim 1, characterized in that: The preparation method of the outer layer filled porous ceramic comprises: placing the middle layer filled porous ceramic into a fluidized bed, introducing nitrogen, then placing a composite sulfur-carbon material preheated to 60° C. into the fluidized bed, atomizing a sodium lignin sulfonate gel precursor liquid through a two-fluid nozzle, and uniformly spraying it at a rate of 0.2-0.4 mL / min; immediately starting a liquid nitrogen cooling system after the spraying is completed to obtain the outer layer filled porous ceramic; the mass ratio of the middle layer filled porous ceramic, the composite sulfur-carbon material, and the sodium lignin sulfonate gel precursor liquid is 8:(1-1.2):(0.2-0.4).

8. The method for preparing a porous ceramic-loaded sulfur-based composite filler according to claim 1, characterized in that: The gradient heat treatment includes: placing the outer layer filled porous ceramic into a programmable temperature-controlled furnace, heating the material to 100-120°C at a rate of 5-8°C / min and keeping the temperature for 30-40 minutes under a nitrogen atmosphere, further heating the material to 140-160°C and keeping the temperature for 20-30 minutes, then heating the material to 200-220°C at a rate of 10°C / min and keeping the temperature for 10-15 minutes, and finally cooling the material to room temperature.

9. The method for preparing a porous ceramic-loaded sulfur-based composite filler according to claim 1, characterized in that: The pickling treatment includes: placing the outer filling porous ceramic that has undergone the gradient heat treatment into a drum-type reactor, spraying 5-8wt% citric acid solution while rolling, the mass ratio of citric acid solution to the outer filling porous ceramic being (0.5-2):1, and obtaining the porous ceramic-loaded sulfur-based composite filler after drying.

10. Use of a porous ceramic-supported sulfur-based composite filler prepared by the preparation method according to any one of claims 1 to 9 in wastewater denitrification and phosphorus removal.

Citation Information

Patent Citations

  • Microelectrolysis-sulfur autotrophic denitrification sintering-free filler as well as preparation method and application thereof

    CN116332344A

  • Red mud-based sewage treatment agent, preparation method therefor, red mud-based ceramsite concrete, preparation method for same, and applications thereof

    WO2021168995A1

Cited By

  • Sulfur element slow-release carrier for biochemical denitrification and preparation method of sulfur element slow-release carrier

    CN121318007A